Identification of unique DNA sequences in Aquilaria malaccensis and Aquilaria hirta via genomic representational difference anaylsis (RDA) - Noorhidayah, Md Nazir (2014)
Aquilaria species that are listed among the endangered plant species are well known as the main agarwood producers in the world. Agarwood produced by Aquilaria spp. has been widely used in traditional medicine, incenses for religious rituals and also in perfumery industry. However, identification of the species in Aquilaria genus is very challenging due the changing of their morphological structures that are highly dependent on the changes of environmental conditions. Thus, this study was aimed to identify the unique DNA sequences that are available in the genome of Aquilaria malaccensis and A. hirta to be used as specific molecular markers for species identification purpose. Genomic Representational Difference Analysis (RDA) was applied by amplifying DNA sequences that are only available in the genome of interest species while eliminating DNA sequences that are redundant in both interest and noninterest genomes. A number of three rounds of RDA with different ratios of “tester” and “driver” DNA were carried out and finally, 15 unique DNA sequences were successfully isolated from the final round of RDA. The isolated sequences were sequenced and subjected to BLASTN analysis for identification and prediction of their functional role based on their similarity to homologous DNA sequences that are available in the NCBI GenBank database. From the BLASTN analysis, majority of the sequences did not match to any sequence that is available in the database. This might be due to the lacking of information discovered and reported on Aquilaria spp. in molecular biology as well as bioinformatics aspects. Based on the isolated sequences, different set of gene specific primers were designed specifically for each potential sequence. The primers were subsequently applied in PCR amplification of the unique DNA sequences directly from genomic DNA of selected Aquilaria spp. for confirmation of the presence of the DNA sequences uniquely in species of interest while absence in the other Aquilaria spp.. From the confirmation, 12 unique DNA sequences have shown their potential to be used as molecular markers in A. hirta while in A. malaccensis, there are only three identified potential sequences to be used as molecular markers. The isolated unique DNA sequences will be very useful for Aquilaria spp. identification that will benefit agarwood plantation industry in order to produce and maintain a good quality of agarwood for fragrance and perfumery industries.